2020
DOI: 10.29374/2527-2179.bjvm112020
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal/stem cells: historical perspective and ongoing challenges

Abstract: The potential of stem cell-based therapy was accompanied by high expectations and led, consequently, to an increase in clinical translational investments. Mesenchymal stem/stromal cells (MSCs) became the cell-based product most experimentally studied worldwide. However, uncertainties about the mechanisms and the in vivo identity of MSCs impose concerns about their large-scale use in regenerative medicine. This review comprises a historical summary on MSC, a critical discussion about their identity and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…Guimarães-Camboa and colleagues showed that pericytes and vascular smooth muscle cells, although multipotent in vitro, do not behave as MSCs in vivo [94]. These findings contrast with previous studies that also used lineage tracing assays and give rise to an ongoing debate regarding the progenitor hierarchy between MSCs and pericytes [94,108]. Both MSCs and pericytes take an active role in the formation of the PMN.…”
Section: Mscsmentioning
confidence: 86%
“…Guimarães-Camboa and colleagues showed that pericytes and vascular smooth muscle cells, although multipotent in vitro, do not behave as MSCs in vivo [94]. These findings contrast with previous studies that also used lineage tracing assays and give rise to an ongoing debate regarding the progenitor hierarchy between MSCs and pericytes [94,108]. Both MSCs and pericytes take an active role in the formation of the PMN.…”
Section: Mscsmentioning
confidence: 86%
“…In addition to the ability to differentiate, these cells are of great importance in regenerative medicine owing to their ability to mediate the immune response in injured tissues, e.g., immunomodulation for tissue regeneration (Miao et al, 2006). However, their characterization and clinical use remains challenging (Rossi & Bonfim, 2020).…”
Section: Ys-derived Mesenchymal Stem Cellsmentioning
confidence: 99%